Perlindungan Usaha Kecil Menengah dalam Undang-Undang Persaingan Usaha - Safrina Safrina; Susiana Susiana (Kanun Jurnal Ilmu Hukum, 2013)
ABSTRACT: The law of Prohibition of Monopolistic Practices and Unfair Business Competition Number 5   1999 (Competition Law) is one of the government's efforts to provide business certainty for businesses in a situation of fair competition and reasonable, so it does not cause the concentration of economic power in the business operators particular. This study aims to explain the legal protection of the Small and Medium Enterprises (SMEs) in Indonesia competition law and to find out the role of local government, Banda Aceh and Aceh Besar, in support of the protection efforts, especially related to the expansion by the Pante Pirak Company. The study combines two methods of juridical normative and empirical (sociology). Analysis of the qualitative approach and descriptive analysis presented; analyze the protection of SMEs under the competition law and then combine with field research to understand the role of local governments in support of such protection. Research shows that there are no provisions in competition law which expressly provides support to SMEs, but the shape is visible through decision support by Komite Pengawas Persaingan Usaha (KPPU). Local government support to SMEs has not been realized in the form of the laws, but there have been efforts to better support local businesses rather than national employers through policies. Even though its casuistry and very difficult to ensure its sustainability. Protection of Small and Medium Enterprises in Indonesia Competition Law